ANALISIS PENGARUH KOMPONEN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI SUMATERA UTARA TAHUN 2021-2022 - Quarthano Reavindo; Irsad Lubis (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This research aims to find out how much influence the Human Development Index has on the poverty level in North Sumatra in 2021-2022. This research uses secondary data sourced from the North Sumatra Central Statistics Agency. To process the data in this research, we use a panel data regression model using a computer program in the form of E-Views 13. This model was chosen because the data in this research is panel data, namely a combination of cross section data and time series data. The data panel used is data from 33 districts/cities in North Sumatra for the period 2021-2022. From the results of this research, it can be concluded that all components in the Human Development Index, namely life expectancy, average years of schooling, expected years of schooling, and adjusted per capita expenditure have a negative influence on the percentage of poor people in North Sumatra.